Pain management and the effect of guidelines in neonatal units in Austria, Germany and Switzerland - Gharavi, Bahman; Schott, Claus; Nelle, Mathias; Reiter, Gernot; Linderkamp, Otwin (Pediatrics international, 2007)
Background: Painful invasive procedures are frequently performed on preterm infants admitted to a neonatal intensive care unit (NICU). The aim of the present study was to investigate current pain management in Austrian, German and Swiss NICU and to identify factors associated with improved pain management in preterm infants. Methods: A questionnaire was sent to all Austrian, German and Swiss pediatric hospitals with an NICU (n = 370). Pain assessment and documentation, use of analgesics for 13 painful procedures, presence of written guidelines for pain management and the use of 12 analgesics and sedatives were examined. Results: A total of 225 units responded (61%). Pain assessment and documentation and frequent analgesic therapy for painful procedures were performed more often in units using written guidelines for pain management and in those treating >50 preterm infants at <32 weeks of gestation per year. This was also the case for the use of opioid analgesics and sucrose solution. Non-opioid analgesics were used more often in smaller units and in units with written guidelines. There was a broad variation in dosage of analgesics and sedatives within all groups. Conclusion: Pain assessment, documentation of pain and analgesic therapy are more frequently performed in NICU with written guidelines for pain management and in larger units with more than 50 preterm infants at <32 weeks of gestation per year.